Carrot and sticks strategy: does it work to motivate employees to be green? - Rozaidy Mahadi; Siti Nabiha Abdul Khalid (IIUM Press, 2014)
The sustainability of the hotel industry depends heavily on the preservation of natural beauty of the country. However, hotels’ non-friendly environmental practices have been responsible for directly polluting the environment. The pressure from environmental or green movements has enhanced many hotels’ environment. However, changes in operational processes and systems alone are not good enough to reduce their environmental impact. Besides putting in place suitable environmental management practices, a change in human behavior is believed to be necessary. Personnel and cultural controls strategy in management control system is synonym as a carrot and stick approach that is prescriptively utilized to enticing elicit desired behavior. Therefore, the case study tries to advocate the changes that require proper planning and the commitment from the business operators that are vitally important to ensure the employees sustainably carry out the hotel’s environmental practices.